ЎРХУН-ЕНИСЕЙ ЁЗУВЛАРИ МОҲИЯТИНИ ТАЛҚИН ЭТИШНИНГ АҲАМИЯТИ - Назаров, Н.А. (SCIENCE and SOCIETY, 2020)
The article considers Orkhon-Yenisey written monuments as ancient Turkic writing and points out the importance of the modern interpretation of its essence. Examples from inscriptions are given, and also attention is paid to their content. Emphasis is placed on the mechanisms of promoting the ideas of Turkic runology, focusing attetion on the aspects of increasing national and common Turkic thinking and ensuring mutual understanding based on historical ideas. It also explores the promising aspects of the study of Turkic runology.